MAKNA SIMBOLIK RELIEF SUDAMALA DAN GARUDEYA DI CANDI SUKUH RELEVANSINYA DENGAN PENGEMBANGAN NILAI-NILAI KARAKTER DALAM PEMBELAJARAN IPS SEJARAH - Wardani, Yuliana Kuncoro (Candi, 2013)
The aims of this study are to describe (1) the meaning of Sudamala and Garudeya reliefs in Sukuh Temple, (2) the value transformation in Sudamala and Garudeya reliefs in Sukuh Temple with the development of character values, (3) the values relevance in the Sudamala and Garudeya reliefs in Sukuh Temple to the character values in history learning. This study is a qualitative descriptive study. This study used single embedded case study strategy. Data sources used in this study were objects, places, events, informants, and documents sources. The sampling techniques used were purposive and snowball sampling. In testing the data validity, the writer used two triangulation techniques, including data triangulation and method triangulation. The results of this study show that: (1) The Sudamala reliefs in Sukuh Temple have a meaning of Sadewa, who has released Durga Ra Nini from Hyang Guru?s curse, where as Garudeya reliefs in Sukuh Temple have a meaning of Garudeya, who released his mother (Dewi Winata) from her slave status from Dewi Kadru by using Tirta Amerta, (2) the values transformation in the Sudamala and Garudeya reliefs by the developing of character values the Educational and Cultural Department expressed, can be identified some character values including  religious, honest, hard-working, tolerant, responsible, friendly/ communicative, democratic, socially care, creative, discipline, and autonomous, (3) the existing values in the Sudamala and Garudeya reliefs in Sukuh Temple have a relevance to the social sciences learning through the history learning materials, which can be seen in the Competence Standard and Basic Competence of the seventh until the ninth grades, especially in the Competence Standards and Basic Competences of the second semester of the seventh grade, that are ?understanding the society development since the Hinduism-Buddhism period until the European Colonialism period? and ?describing the societal, cultural, and governmental development in Hinduism-Buddhism period and its heritance? Basic Competences, with some character values, such as: religious, honest, hard-working, tolerant, responsible, friendly/ communicative, democratic, socially care, creative, discipline, and autonomous.